Activity Measures in Pediatric Athletes: A Comparison of the Hospital for Special Surgery Pediatric Functional Activity Brief Scale and Tegner Activity Level Scale. Issue 4 (March 2020) - Wagner, K. John; Sabatino, Meagan J.; Zynda, Aaron J.; Gans, Catherine V.; Chung, Jane S.; Miller, Shane M.; Wilson, Philip L.; Ellis, Henry B.
Background: In young athletes, patient-reported activity level is frequently used to determine return to the same level of sport after treatment. Purpose: To evaluate the validity and score distributions of the Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS) compared with the Tegner Activity Level Scale (Tegner) in pediatric athletes. Study Design: Cohort study (Diagnosis); Level of evidence, 2. Methods: A retrospective review of 517 consecutive youth athletes who came to a sports medicine specialty clinic for a knee evaluation was performed. Patients completed the HSS Pedi-FABS, Tegner, and a sports participation survey before evaluation. Scores were compared with reported hours, days, and weeks of participation in sports as well as level of competition. Floor or ceiling effects were identified, and finally, the means and distributions of scores in the 8 most common primary sports were analyzed. Results: A total of 398 participants (54.0% female) with an average age of 14.5 years (range, 10.0-18.8 years) were included in the study. The HSS Pedi-FABS demonstrated correlations with hours per week ( r = 0.302; P < .001), days per week ( r = 0.278; P < .001), and weeks per year ( r = 0.136; P = .014) playing a primary sport. The Tegner only demonstrated a correlation with days per week ( r = 0.211; P = .001). Additionally, club/select-level athletes scored higher than junior high/high school–level athletes on the HSS Pedi-FABS (23.8 vs 21.0; P = .004), but no difference was observed with the Tegner. No floor or ceiling effect was observed for the HSS Pedi-FABS, but a ceiling effect was present for the Tegner (32.8%). The HSS Pedi-FABS demonstrated a varied score distribution between the 8 most common primary sports ( P < .001), with soccer players scoring the highest, on average (23.5). Conclusion: The HSS Pedi-FABS, compared with the Tegner, demonstrated more correlations with an athlete's participation in sport with no floor or ceiling effect and had a wide distribution of scores even among same-sport athletes. The HSS Pedi-FABS may be a more valuable activity measure than the Tegner in pediatric athletes.